Crosstalk between the aging intestinal microflora and the brain in ischemic stroke - Pluta, Ryszard; Jabłoński, Mirosław; Januszewski, Sławomir; Czuczwar, Stanisław J. (Frontiers in Aging Neuroscience, 2022)
Aging is an inevitable phenomenon experienced by animals and humans, and its intensity varies from one individual to another. Aging has been identified as a risk factor for neurodegenerative disorders by influencing the composition of the gut microbiota, microglia activity and cognitive performance. The microbiota-gut-brain axis is a two-way communication path between the gut microbes and the host brain. The aging intestinal microbiota communicates with the brain through secreted metabolites (neurotransmitters), and this phenomenon leads to the destruction of neuronal cells. Numerous external factors, such as living conditions and internal factors related to the age of the host, affect the condition of the intestinal microflora in the form of dysbiosis. Dysbiosis is defined as changes in the composition and function of the gut microflora that affect the pathogenesis, progress, and response to treatment of a disease entity. Dysbiosis occurs when changes in the composition and function of the microbiota exceed the ability of the microflora and its host to restore equilibrium. Dysbiosis leading to dysfunction of the microbiota-gut-brain axis regulates the development and functioning of the host’s nervous, immune, and metabolic systems. Dysbiosis, which causes disturbances in the microbiota-gut-brain axis, is seen with age and with the onset of stroke, and is closely related to the development of risk factors for stroke. The review presents and summarizes the basic elements of the microbiota-gut-brain axis to better understand age-related changes in signaling along the microbiota-gut-brain axis and its dysfunction after stroke. We focused on the relationship between the microbiota-gut-brain axis and aging, emphasizing that all elements of the microbiota-gut-brain axis are subject to age-related changes. We also discuss the interaction between microbiota, microglia and neurons in the aged individuals in the brain after ischemic stroke. Finally, we presented preclinical and clinical studies on the role of the aged microbiota-gut-brain axis in the development of risk factors for stroke and changes in the post-stroke microflora.